Physiological responses of broiler chickens to heat stress and dietary electrolyte balance (sodium plus potassium minus chloride, milliequivalents per kilogram) - Borges, S. A. [UNESP]; Fischer Da Silva, A. V. [UNESP]; Majorka, A. [UNESP]; Hooge, D. M.; Cummings, K. R. (Elsevier, 2004)
Individually caged male Cobb broilers (24), 44 d of age, were used to evaluate effects of heat stress (1 d of data collection) and dietary electrolyte balance (DEB; Na + K - Cl, mEq/kg from 1 d of age). During summer rearing, mortality was variable, but DEB 240 improved growth, feed conversion ratio, water intake, and waterrfeed ratio vs. DEB 0. The temperature sequence for heat stress was 24 to 32°C in 30 min, 32 to 36°C in 30 min, 36 to 37°C in 15 min, and 37 to 41°C in 45 min. Maximum temperature was held for 15, 60, 90, or 360 min for data collection (relative humidity averaged 42 ± 7%). Results from the same room before and after heat stress were analyzed by DEB (1-factor ANOVA) and before vs. after heat stress compared across DEB (2-sample t-test). Heat stress decreased blood Na, K, and pCO2, and lymphocytes but increased heterophils. Blood HCO3 rose, Cl declined, and hematocrit gave a concave pattern (lowest at DEB 120) as DEB increased. After heat stress, DEB O decreased blood Na and K, and DEB O and 120 levels decreased blood HCO3. After heat stress blood pCO2 and hemoglobin decreased with DEB 240, but it had highest pCO2, a key factor. The DEB 120 gave longest times to panting and prostration with DEB O and 240 results lower but similar statistically. In heat stress, DEB 360 was excessive, DEB 120 and 240 were favorable, and DEB 0 was intermediate based on hematology, panting, and prostration responses.
Keywords: Alkalosis; Broiler; Electrolyte balance; Heat stress; Hematology; carbon dioxide; electrolyte; hemoglobin; acid base balance; adaptation; animal; blood; body temperature; chicken; cytology; diet; drinking; electrolyte balance; growth; heat exhaustion; heat injury; lymphocyte; male; neutrophil; pathophysiology; physiology; respiratory function; Acid-Base Equilibrium; Adaptation, Physiological; Animals; Body Temperature; Carbon Dioxide; Chickens; Diet; Drinking; Electrolytes; Growth; Heat Exhaustion; Heat Stress Disorders; Hemoglobins; Lymphocytes; Male; Neutrophils; Respiratory Physiologic Phenomena; Water-Electrolyte Balance; Gallus gallus